2002
DOI: 10.1093/nar/gkf652
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of site-specific recombination by the C-terminus of lambda integrase

Abstract: Site-specific recombination catalyzed by bacteriophage lambda integrase (Int) is essential for establishment and termination of the viral lysogenic life cycle. Int is the archetype of the tyrosine recombinase family whose members are responsible for DNA rearrangement in prokaryotes, eukaryotes and viruses. The mechanism regulating catalytic activity during recombination is incompletely understood. Studies of tyrosine recombinases bound to their target substrates suggest that the C-termini of the proteins are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
2
37
3
Order By: Relevance
“…One of the most useful mutants for studying the role of the C-terminal tail is a deletion of the seven most distal residues (W350ter), which results in a hyperactive topoisomerase (14,15,20,21). Previous results indicating that W350ter is similar to wild-type Int in its ability to cleave both half-and full-att suicide substrates (14) contrasts with the results from our laboratory.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…One of the most useful mutants for studying the role of the C-terminal tail is a deletion of the seven most distal residues (W350ter), which results in a hyperactive topoisomerase (14,15,20,21). Previous results indicating that W350ter is similar to wild-type Int in its ability to cleave both half-and full-att suicide substrates (14) contrasts with the results from our laboratory.…”
Section: Discussioncontrasting
confidence: 66%
“…These structures, as well as a considerable amount of genetic and biochemical data, indicate that the C-terminal residues of each recombinase participate in trans (intermolecular) interactions that seem to have a regulatory function, albeit by different mechanisms in each system (8,(10)(11)(12)(13). Some of the experiments in this report are designed to reconcile and expand on the existing structural, genetic, and biochemical data pertaining to the role of the C-terminal tail of Int (6,7,(14)(15)(16).Despite many years of genetic and biochemical studies on the Int recombination system, it is still not known whether the Int recombinase is competent for DNA cleavage as a monomer. When Kikuchi and Nash first purified Int, they showed that at high salt it is a monomer in solution (17).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…We believe that these aberrant hairpin products arise from uncoordinated DNA cleavages at "non-partner" Int binding sites, either during or after resolution. 14,16 These findings extend previous results 2, 3,5,6 indicating that while the C-terminal tail is not required for DNA cleavage by monomeric Int, it plays a critical role in the function and proper coordination of multimeric Int.…”
Section: C-terminal Tail Is Required For Efficient and Coordinated Hosupporting
confidence: 73%
“…The phage-encoded integrase is a heterobivalent DNA-binding protein. It consists of a large C-terminal domain that binds to core-type DNA sequences and carries out the enzymatic steps of recombination (11,12). Additionally, Int contains a small N-terminal domain that binds to arm-type DNA sites that are distant from the sites of DNA strand exchange (13).…”
mentioning
confidence: 99%